DEVELOPING ANDROID-BASED BILINGUAL E-GLOSSARY FOR BUSINESS ADMINISTRATION STUDENTS - Moch. Fauzi Rianto (Jurnal Linguistik Terapan, 2022)
This research is a Design and Development Research. The aim of this research is a creation of a bilingual e-glossary application for Business Administration. The motives of the research are (1) to develop an Android-based bilingual glossary application in the field of Business Administration; (2) to give preferable solutions to the problems which students of Business Administration Department often face. During the process of this research, there were five phases to develop the product; analysis, design, development, implementation, and evaluation. The outcome of this research was a bilingual e-glossary for Business Administration which utilized a mobile device as the platform. The product of this research is advantageous for Business Administration students, learners who study in the field of Business Administration, and for D3 Program in Applied English at State Polytechnic of Malang.